2020
DOI: 10.1007/978-1-0716-0712-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Development and Applications of Fluorogen/Light-Up RNA Aptamer Pairs for RNA Detection and More

Abstract: The central role of RNA in living systems made it highly desirable to have non-invasive and sensitive technologies allowing for imaging the synthesis and the location of these molecules in living cells. This need motivated the development of small pro-e ce ec e ca ed e a bec e e ce b d e e ca e c dab e RNA ca ed-a a e. Ye , e development of these fluorogen/light-up RNA pairs is a long and thorough process starting with the careful design of the fluorogen and pursued by the selection of a specific and efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 135 publications
(189 reference statements)
0
5
0
Order By: Relevance
“…Various aptamers now can be routinely engineered through repeated rounds of in vitro selection, also known as systematic evolution of ligands by exponential enrichment (SELEX), the powerful technique that was developed in the early 1990s. , Since then, numerous different types of aptamers against different target molecules have been selected in academic research laboratories and have found applications in various biotechnological fields. In particular, the fluorogenic RNA aptamers are known for their specificity in binding otherwise nonfluorescent dyes; the fluorescent emission of the dye is activated only upon binding to its RNA aptamer. This binding specificity enabled the design not only of label-free nucleic-acid-based sensors in vitro but also the attractive development of binary 1 and 0 systems, as shown in Figure D,E. , The input signal induces the conformational change of the fluorophore-binding pocket (analogous to a “gate”), dictating the overall affinity strength of the RNA–fluorophore complex. Various factors can potentially serve as inputs, including single-stranded oligonucleotides and nonfluorescent molecules mimicking structures of the ligand dye.…”
Section: On Dynamic Structures and Logic Gatingmentioning
confidence: 99%
“…Various aptamers now can be routinely engineered through repeated rounds of in vitro selection, also known as systematic evolution of ligands by exponential enrichment (SELEX), the powerful technique that was developed in the early 1990s. , Since then, numerous different types of aptamers against different target molecules have been selected in academic research laboratories and have found applications in various biotechnological fields. In particular, the fluorogenic RNA aptamers are known for their specificity in binding otherwise nonfluorescent dyes; the fluorescent emission of the dye is activated only upon binding to its RNA aptamer. This binding specificity enabled the design not only of label-free nucleic-acid-based sensors in vitro but also the attractive development of binary 1 and 0 systems, as shown in Figure D,E. , The input signal induces the conformational change of the fluorophore-binding pocket (analogous to a “gate”), dictating the overall affinity strength of the RNA–fluorophore complex. Various factors can potentially serve as inputs, including single-stranded oligonucleotides and nonfluorescent molecules mimicking structures of the ligand dye.…”
Section: On Dynamic Structures and Logic Gatingmentioning
confidence: 99%
“…17,19,20,21 The Mango II aptamer contains a well-de ned but plastic pocket capable of binding TO derivatives in multiple orientations. To date, most work on the Mango system has focused on evolution of improved aptamers, 22,23 development of uorogenic transcripts for live cell or single molecule imaging, 24 or rational modi cation of the TO uorophore to alter excitation/emission pro les. 25 The discovery of Mango aptamers represents a powerful advance in the development of RNA imaging tools.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent light-up aptamers have emerged as powerful tools for visualizing the dynamics of RNA expression in living cells [1][2][3] and providing a bright, translation-free readout for in vitro reactions [4][5][6] . These systems consist of short sequences of RNA or DNA that bind to conditionally fluorescent dye molecules known as fluorogens to activate their fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…These systems consist of short sequences of RNA or DNA that bind to conditionally fluorescent dye molecules known as fluorogens to activate their fluorescence. Since the 2003 discovery of the MG RNA aptamer for binding malachite green 7 , diverse aptamer/fluorogen pairs have been developed with high binding specificity and varying spectral and photophysical properties 1 . In 2014, Jaffrey et al reported the Broccoli aptamer that binds to the GFP-mimicking fluorogen DFHBI-1T and provides robust folding and green fluorescence in living cells 8 .…”
Section: Introductionmentioning
confidence: 99%